Peningkatan Kompetensi Akademik Guru TK dan PAUD Melalui Pelatihan Google Classroom - Sarbaini Sarbaini; Eka Pandu Cynthia; Fitriani Muttakin; M. Imam Arifandy (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
The condition of a pandemic spreading the Covid-19 virus that occurred in Indonesia in early 2019 inevitably caused the dynamics of a shift in the learning model from outdoor/face-to-face to online/virtual, as well as various monthly activities in the form of workshops and other activities. to improve the competence of all teacher educators in the Sakura Cluster environment. The purpose of this activity is that Kindergarten/PAUD teachers in Cluster VI Sakura can get to know google classroom and implement google classroom and assist in teaching and learning activities that are carried out online. The method of implementing the activities carried out in this activity with reference to the problem solving framework previously described, namely varied lectures. The results of this community service activity include increasing the skills of kindergarten/PAUD teachers who are gathered in Cluster VI Sakura, Tenayan Raya District, Pekanbaru City in using and utilizing technology and GAFE (especially google classroom) for the learning and teaching process, especially now that is done online.